Argentine tango in Parkinson disease – a systematic review and meta-analysis. Issue 1 (December 2015) - Lötzke, Désirée; Ostermann, Thomas; Büssing, Arndt
Abstract Background Parkinson's Disease (PD) is a neurodegenerative disease with increasing motor and non-motor symptoms in advanced stages. In addition to conventional exercise therapy and drug treatment, Argentine Tango (AT) is discussed as an appropriate intervention for patients to improve physical functioning and health-related quality of life. This review aimed to summarize the current research results on the effectiveness of AT for individuals with PD. Methods The global literature search with the search terms "(Parkinson OR Parkinson's disease) AND tango" was conducted in PubMED, AMED, CAMbase, and Google Scholar for publications in English and German. There were no limitations on the study design, year of publication, stage of disease, considered outcome or the age of participants. Results Thirteen studies met the inclusion criteria. These included 9 randomized-controlled trials, one non-randomized trial, two case studies and one uncontrolled pre-post study. Our meta-analysis revealed significant overall effects in favor of tango formotor severity measured with the Unified Parkinson's Disease Rating Scale 3 (ES = −0.62, 95 % CI [−.1.04, −0.21]), balance as measured with the Mini-BESTest (ES = 0.96 [0.60, 1.31]) or Berg Balance Scale (ES = 0.45 [0.01, 0.90]), andgait with the Timed Up and Go Test (ES = −.46 [−0.72, −0.20]). However, gait as measured with a 6-Minute Walk Test did not demonstrate statistical significance (ES = 0.36 [−0.06, 0.77]). Forfreezing of gait, no significant effects were observed in favor of AT (ES = 0.16 [−.62, 0.31]). Further, our systematic review revealed a tendency for positive effects on fatigue, activity participation and Parkinson-associated quality of life. A limitation of the studies is the small number of participants in each study (maximum 75). Moreover, most studies are from the same research groups, and only a few are from other researchers. Conclusions Future studies should enroll more individuals and should also focus on long-term effects. In addition, future research should address more closely the effects of AT on personal relationships, the individual social network as well as on aspects of quality of life.